Leading issues in competition, regulation, and development - Cook, Paul, 1944-; Edward Elgar Publishing (Cheltenham, U.K. ; Northampton, Mass. : Edward Elgar, 2004)
The book draws together contributions from leading experts across a range of disciplines including economics, law, politics and governance, public management and business management. The authors begin with an extensive overview of the issues of regulation and competition in developing countries, and carefully illustrate the important themes and concepts involved. Using a variety of country and sector case studies, they move on to focus on the problems of applicability and adaptation that are experienced in the process of transferring best practice policy models from developed to developing countries. The book presents a clear agenda for further empirical research and is notable for its rigorous exploration of the links between theory and practice.
pt. 1. Competition and regulation in developing countries : an overview, pt. 2. Competition, regulation and development : leading concepts and issues -- pt. 3. Competition and regulation in developing countries : policies and practice.
Includes bibliographical references and index.
Keywords: Industrial policy -- Developing countries; Trade regulation -- Developing countries; Competition -- Developing countries; Competition, International; Developing countries -- Foreign economic relations; Electronic books